2012
DOI: 10.1673/031.012.3101
|View full text |Cite
|
Sign up to set email alerts
|

Mygalomorph Spider Community of a Natural Reserve in a Hilly System in Central Argentina

Abstract: The diversity, abundance, spatial distribution, and phenology of the mygalomorph spider community in the “Ernesto Tornquist” Strict Nature Reserve were analyzed in this study. Located in southwestern Buenos Aires, Argentina, the Reserve is representative of the Ventania system, which is a sigmoidal mountain belt 180 km in length. This exceptional hilly ecosystem is home for many endemic species and rich native fauna and flora. Spider abundance was sampled monthly from October 2009 to October 2010 by hand captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
2
26
0
7
Order By: Relevance
“…spiderlings was discovered inside the container. The period of spiderling emergence (during March) was the same as that reported in the field for an Actinopus species from the Ventania hilly system in southern Buenos Aires province (Ferretti et al 2012). The lengths of 46 spiderlings from the dispersal aggregation, including chelicerae and spinnerets, averaged 3.58 mm (range 3.1-4.3 mm).…”
mentioning
confidence: 59%
“…spiderlings was discovered inside the container. The period of spiderling emergence (during March) was the same as that reported in the field for an Actinopus species from the Ventania hilly system in southern Buenos Aires province (Ferretti et al 2012). The lengths of 46 spiderlings from the dispersal aggregation, including chelicerae and spinnerets, averaged 3.58 mm (range 3.1-4.3 mm).…”
mentioning
confidence: 59%
“…Acanthogonatus centralis Goloboff 1995 (Nemesiidae) is a mygalomorph spider that inhabits the hilly areas of central Argentina and constructs tunnel webs connected to a short burrow under stones. Ferretti et al (2012) reported on the unusually high motility of adult males, females, and juveniles of this species in the field; thus the probability of encounter between females is highlighted.…”
Section: Introductionmentioning
confidence: 96%
“…En Argentina es escaso el conocimiento que se tiene de la biodiversidad, especialmente de aquellos lugares donde existe una pérdida sistematizada de una gran cantidad de hábitats naturales. En el país se han realizado pocos trabajos referidos a la araneofauna en áreas naturales (Ávalos et al 2007, Rubio et al 2008, Ferretti et al 2010, 2012, Grismado et al 2011, Marfil et al 2016. El presente trabajo, por lo tanto, es el primer estudio de la familia Theridiidae en diferentes ambientes de la Reserva Natural e Histórica "Isla Martín García", donde además se analizó su riqueza específica, su abundancia relativa, y se estimó su diversidad alfa y beta.…”
Section: Introductionunclassified